ESPN : the making of a sports media empire - Vogan, Travis (Urbana : University of Illinois Press, 2015)
Once a shoestring operation built on plywood sets and Australian rules football, ESPN has evolved into a media colossus. A genius for cross-promotion and its near-mystical rapport with its viewers empower the network to set agendas and create superstars, to curate sports history even as it mainstreams the latest cultural trends. Travis Vogan teams archival research and interviews with an all-star cast to pen the definitive account of how ESPN turned X's and O's into billions of $$$. Vogan's institutional and cultural history focuses on the network since 1998, the year it launched a high-motor effort to craft its brand and grow audiences across media platforms. As he shows, innovative properties like SportsCentury, ESPN The Magazine, and 30 for 30 built the network's cultural cache. This credibility, in turn, propelled ESPN's transformation into an entity that lapped its run-of-the-mill competitors and helped fulfill its self-proclaimed status as the "Worldwide Leader in Sports." Ambitious and long overdue, ESPN: The Making of a Sports Media Empire offers an inside look at how the network changed an industry and reshaped the very way we live as sports fans. -- Publisher description.
Introduction : An ESPN culture -- From the Entertainment and Sports Programming Network to ESPN -- SportsCentury : programming public sport history -- ESPN the magazine and Page 2 : paper and digital sports pages -- ESPN original entertainment : branding authority across genres -- ESPN films : "unprecedented documentary series" by "filmmaking originals" -- Grantland : ESPN's Miramax -- Conclusion : From Frontline to the bottom line -- Appendix A. The Entertainment and Sports Programming Network's first press release -- Appendix B. SportsCentury top one hundred athletes of the twentieth century -- Appendix C. SportsCentury panel.
Includes bibliographical references and index.
Keywords: ESPN (Television network) -- History; Television broadcasting of sports -- History